2021
DOI: 10.1002/emp2.12395
|View full text |Cite
|
Sign up to set email alerts
|

Safety of early norepinephrine infusion through peripheral vascular access during transport of critically ill children

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…A small subgroup of 20 children, mostly with septic shock, received an infusion of peripheral norepinephrine for a median time of 660 minutes without the development of extravasation injury. This observation is consistent with findings of Lampin et al (18) and, more recently, Charbel et al (19), who describe 37 children receiving norepinephrine for a median duration of 240 minutes with one extravasation event.…”
Section: Discussionsupporting
confidence: 92%
“…A small subgroup of 20 children, mostly with septic shock, received an infusion of peripheral norepinephrine for a median time of 660 minutes without the development of extravasation injury. This observation is consistent with findings of Lampin et al (18) and, more recently, Charbel et al (19), who describe 37 children receiving norepinephrine for a median duration of 240 minutes with one extravasation event.…”
Section: Discussionsupporting
confidence: 92%
“…For fluid resuscitation, including transfusion of blood products, the flow rates of IO accesses are limited, and at least two peripheral IV lines are recommended, while the size of the cannulas should be large enough to deliver appropriate volumes rapidly [ 1 , 2 , 5 , 6 , 37 ]. Recent studies revealed that continuous administration of vasopressor agents through peripheral IV lines is feasible and safe [ 38 , 39 , 40 ]. However, special attention should be paid to the patency, functionality and securement of peripheral IV lines to avoid extravasation injuries.…”
Section: Discussionmentioning
confidence: 99%
“…11 Preterm neonates born less than 37 gestational weeks are often selected against NE because they are evidenced to present the following: (1) a higher catecholamine level, indicating a presumably weaker response to NE 12 13 ; (2) increased risk of pulmonary hypertension after NE 14 ; (3) an increased vascular resistance and decreased organ perfusion (previously reviewed 15 16 ); and (4) risk of extravasation and skin injury with NE infusion. 17 NE is currently used in less than 5% of preterm neonates with shock 3 as a second-line or third-line treatment. 18 Recent studies have suggested that the adverse events of NE are generally tolerated, and improved haemodynamics after NE can be observed in preterm neonates with septic shock or cardiovascular compromise.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In addition, previous studies in adults showed that dopamine administration might be associated with increased mortality in shock10 or similar outcomes but higher adverse events 11. Preterm neonates born less than 37 gestational weeks are often selected against NE because they are evidenced to present the following: (1) a higher catecholamine level, indicating a presumably weaker response to NE12 13; (2) increased risk of pulmonary hypertension after NE14; (3) an increased vascular resistance and decreased organ perfusion (previously reviewed15 16); and (4) risk of extravasation and skin injury with NE infusion 17. NE is currently used in less than 5% of preterm neonates with shock3 as a second-line or third-line treatment 18…”
Section: Introductionmentioning
confidence: 99%